Development of a web-based resource for supporting social workers' decision making in practice. - Moore, Sue; Tschanter, Eva; Rees, Nancy (Office for Learning and Teaching, 2016)
Traditional classroom and work-based learning approaches are often insufficient in preparing social work students for the difficult work of discretionary decision making in professional situations of uncertainty which commonly arise in the context of prescribed rules, procedures and policies. Using narratives developed by experienced practitioners, The authors designed, implemented and evaluated a multimedia scenario-based resource whereby students can decide on a course of action, then analyse and justify their own and others' normative judgements in a variety of authentically complex decision-making situations. Using the same scenarios, the experienced practitioners will then present different possible courses of action and the one that they decided to progress based on a process of clinical reasoning. Students then had the opportunity to compare their decisions with those of more experienced colleagues in the same clinical situation. This learning resource was developed and made available for extension and modification by other discipline groups more broadly.